2021
DOI: 10.1055/s-0041-1740318
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke in Young Adults Caused by Cervical Artery Dissection—A Retrospective Study

Abstract: Background Ischemic stroke is one of the most common causes of death and disability. The most common independent cause is cervical artery dissection, which represents around 20% of all cases of ischemic stroke in young adults. Risk factors for dissection include male gender, migraine (particularly with aura), hyperhomocysteinemia, recent infection, recent history of minor cervical trauma, young age, current smoking status, increased leucocyte count, and shortened activated partial thromboplastin time, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…ICAD is the leading risk factor for ischemic stroke in younger patients. 2 Previous studies have demonstrated that thromboembolism is a potentially dangerous factor for ischemic strokes secondary to ICAD. 6 Therefore, for selected patients with ICAD, treatment with anticoagulative or antiplatelet agents as the primary treatment is effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAD is the leading risk factor for ischemic stroke in younger patients. 2 Previous studies have demonstrated that thromboembolism is a potentially dangerous factor for ischemic strokes secondary to ICAD. 6 Therefore, for selected patients with ICAD, treatment with anticoagulative or antiplatelet agents as the primary treatment is effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, ICAD accounts for more than 10% of strokes in younger patients. 1 , 2 , 3 Although the mechanism of ICAD remains elusive, studies have shown that it is a multifactorial process linked to potential risk factors, such as trauma and genetic predisposition. 4 Current therapeutic strategies for ICAD include intravenous and intra-arterial thrombolysis, antiplatelet medications, anticoagulation, and surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed 11 research papers comprising a total of 4,840 patients. From these finalised studies, we identified two case-control studies [ 2 , 5 ], three case reports [ 6 , 13 , 14 ], three narrative reviews [ 3 , 4 , 9 ], one retrospective observational study [ 1 ], one cohort study [ 12 ], and one experimental study [ 15 ]. All the studies include young patients presenting to the hospital with either TIA or stroke, evaluated to identify HHCY and further MTHFR gene C677T polymorphism, or patients with cervical/vertebral artery dissections, presenting with cervicogenic headache, which were often initially misdiagnosed as migraine with aura, until later returning with more serious outcomes.…”
Section: Reviewmentioning
confidence: 99%
“…Constituting 71% of all strokes, ischemic stroke (IS) is a leading cause of both mortality and disability. Among young adults, aged 18-45 years or 18-50 years, IS accounts for 10 to 18% of all reported cases [ 1 ]. Hence, it is crucial to enhance our comprehension of the risks, causes, and treatment options for IS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation